Influence of Progressive Islamic Da'wah on Economic Empowerment within the Muslim Community - Karimullah, Suud Sarim (Institut Agama Islam Negeri Kerinci, 2023)
The study aims to explore and analyze the impact of progressive Islamic da'wah on economic empowerment in the Muslim community. This study uses literature study methods with an integrative literature analysis approach to collect, evaluate, and compile relevant previous research results with the aim of obtaining comprehensive and in-depth results on the topics discussed. The results of this study stated that progressive Islamic da'wah has a significant impact on economic empowerment in the Muslim community. In this context, progressive da'wah has become an important agent driving changes in economic thought patterns and behavior in Muslim societies. Progressive Islamic da'wah promotes values such as justice, business ethics, inclusion, and equality, which in turn creates an environment that supports economic empowerment. The positive influence of progressive da'wah is seen in increased participation in economic life, increased capacity of individuals and groups to manage financial resources, and their contribution to local and global economic development. Economic empowerment resulting from progressive Islamic da'wah also creates comprehensive social impacts, including improved quality of life, a more sustainable environment, more active political participation, and more inclusive community development.